Interfaith Marriage: Between Pro and Contra In Islamic Jurist's Thought - Suwarjin, Suwarjin (Madania: Jurnal Kajian Keislaman, 2023)
Interfaith marriage is remained a topic of discussion, especially since the appearance of an application to the Constitutional Court (MK/ Mahkamah Konstitusi) for a judicial review of the marriage law. The decision of the Constitutional Court did not satisfy various parties because the application was rejected because the validity of interfaith marriages is the territory of each religion to decide on it. From here, the pros and cons of interfaith marriage reappear. This article aims to examine the pros and cons of the views of Islamic jurists' thoughts on the legitimacy of interfaith marriages, both from classical scholars and from various groups and mass organizations in Indonesia. This article aims to examine the views of the pros and cons of the validity of interfaith marriages, especially in Islam, both from classical scholars and from various groups and mass organizations in Indonesia. The approach used is classical ushul fiqh to analyze and compare the various views and then synthesize and select the most appropriate views. From this study, it was concluded that the view of the majority of scholars who only allow interfaith marriages between Muslims and ahl al-kitab is a view that is more in line with the theory of ushul fiqh. Besides that, marriage between ahl al-kitab men and Muslim women can also be legalized with the qiyas approach, whose illat is wisdom. Perkawinan beda agama masih menjadi wacana yang terus diperbincangkan, apalagi setelah munculnya permohonan ke Mahkamah Konstitusi (MK) untuk melakukan uji materi undang-undang perkawinan. Putusan MK tidak memuaskan berbagai pihak karena permohonan ditolak karena sahnya perkawinan beda agama adalah wilayah masing-masing agama untuk memutusnya. Dari sinilah muncul kembali pro dan kontra pernikahan beda agama. Artikel ini bertujuan untuk mengkaji pro dan kontra dalam pemikiran ahli hukum Islam tentang keabsahan perkawinan beda agama, baik dari kalangan ulama klasik maupun dari berbagai kalangan ormas di Indonesia. Pendekatan yang digunakan adalah ushul fiqh klasik untuk menganalisis dan membandingkan berbagai pandangan kemudian mensintesa dan menyeleksi pandangan yang paling tepat. Dari kajian ini disimpulkan bahwa pandangan mayoritas ulama yang hanya membolehkan perkawinan beda agama antara muslim dengan ahl al-kitab merupakan pandangan yang lebih sejalan dengan teori ushul fiqh. Selain itu perkawinan antara laki-laki ahl al-kitab dengan perempuan muslim juga dapat dilegalkan dengan pendekatan qiyas, yang illatnya adalah hikmah.